3-Tesla Kinematic MRI of the Cervical Spine for Evaluation of Adjacent Level Disease After Monosegmental Anterior Cervical Discectomy and Arthroplasty: Results of 2-Year Follow-Up. Issue 4 (15th February 2017) - Fleck, Steffen K.; Langner, Soenke; Rosenstengel, Christian; Kessler, Rebecca; Matthes, Marc; Müller, Jan-Uwe; Langner, Inga; Marx, Sascha; Schroeder, Henry W.S.
Abstract : Study Design: We prospectively evaluated adjacent disc levels after anterior cervical discectomy and arthroplasty (ACDA) using kinematic magnetic resonance imaging (MRI) and plain functional radiographs. Objective: ACDA is an established treatment for degenerative cervical disc disease. The objective of this study was to evaluate the use of kinematic MRI for assessing the range of motion (ROM) before and after ACDA compared with plain functional radiographs and to evaluate adjacent degenerative disc disease (aDDD) at mid-term follow-up. Summary of Background Data: Twenty patients (12 females, 8 males; median age 45.6 ± 6.9 yrs) treated by ACDA (BryanDisc; Medtronic, MN) underwent plain functional radiography and kinematic MRI of the cervical spine at 3 T before and 6 and 24 months after surgery. Methods: A sagittal T2-weighted (T2w) 2D turbo spin echo (TSE) sequence and a 3D T2w dataset with secondary axial reconstruction were acquired. Signal intensity of all nonoperated discs was measured in regions of interest (ROI). Disc heights adjacent to the operated segment were measured. ROM was evaluated and compared with plain functional radiographs. Clinical outcome was evaluated using the visual analog scale (VAS) for head, neck and radicular pain, and the neck disability index (NDI). Results: Mean ROM of the cervical spine on functional plain radiographs was 21.25 ± 8.19°, 22.29 ± 4.82°, and 26.0 ± 6.9° preoperatively and at 6-month and 24-month follow-up, respectively. Mean ROM at MRI was 27.1 ± 6.78°, 29.45 ± 9.51°, and 31.95 ± 9.58°, respectively. There was a good correlation between both techniques. Follow-up examinations demonstrated no signs of progressive degenerative disc disease of adjacent levels. All patients had clinical improvement up to 24 months after surgery. Conclusion: After ACDA, kinematic MRI allows evaluation of the ROM with excellent correlation to plain functional radiographs. Mid-term follow-up after ACDA is without evidence of progressive DDD of adjacent segments. Level of Evidence: 3